If you want, we'll travel to the moon together : Twaalf verkenningen van kunst en globalisering. - Konz, Judith; Waterhout, Ruud; Batelaan, Lotte; Siemerink, Else; van Aalst, Sasha; Arends, Jacqueline; Ahlers, Jesse; Roosendaal, Saul; Huberts, Irene; Rijnja, Edith; Pols, Cindy; van der Vlies, Roel (s.l. : Digitalis, 2011)
Nijburg, Rinke ; Lombardi, Mark ; Bartana, Yael ; NSK State en Transnational Republic ; Perjovschi, Dan ; Banksy ; Ai Weiwei ; Dinh Q. Lê ; Mik, Aernout ; Samant, Sharmila ; Martens, Renzo ; The Action Mill
boek